2019
DOI: 10.1029/2019jb017926
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Pulse‐Like Earthquake Ruptures

Abstract: Pulse‐like ruptures arise spontaneously in many elastodynamic rupture simulations and seem to be the dominant rupture mode along crustal faults. Pulse‐like ruptures propagating under steady state conditions can be efficiently analyzed theoretically, but it remains unclear how they can arise and how they evolve if perturbed. Using thermal pressurization as a representative constitutive law, we conduct elastodynamic simulations of pulse‐like ruptures and determine the spatiotemporal evolution of slip, slip rate,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 44 publications
(109 reference statements)
0
19
0
Order By: Relevance
“…Numerical calculations have predicted that this coupling gives rise [28,29] to both directional effects as well as to interesting modes of rupture called 'slip pulses' in which slip is highly localized at the rupture tip. We note that slip pulses are not solely generated by bimaterial coupling, they have also been numerically observed under strong velocity weakening of friction [30] that can be induced, for example, by poroeleastic [31] or thermal pressurization [32] effects.…”
Section: Introductionmentioning
confidence: 65%
“…Numerical calculations have predicted that this coupling gives rise [28,29] to both directional effects as well as to interesting modes of rupture called 'slip pulses' in which slip is highly localized at the rupture tip. We note that slip pulses are not solely generated by bimaterial coupling, they have also been numerically observed under strong velocity weakening of friction [30] that can be induced, for example, by poroeleastic [31] or thermal pressurization [32] effects.…”
Section: Introductionmentioning
confidence: 65%
“…Recent studies have demonstrated the inherent instability of slip-pulses for different kinds of friction constitutive laws [22,24,26,34]. These models reported the existence of a steady-state pulse solutions located at the sharp transition between growing pulses, whose spatial extent increases during propagation, and decaying pulses, whose spatial extent progressively shrinks and eventually arrests the pulse.…”
Section: Discussionmentioning
confidence: 99%
“…The ubiquity of pulse-like rupture observed in frictional systems has motivated the development of theoretical and numerical models to investigate the conditions supporting the emergence of slip pulses. Slip-pulses have been found in systems with a large variety of boundary conditions and domain approximations [19][20][21][22][23][24][25][26] and friction laws including from rate-and-state friction [22,23,26], velocity-weakening friction [19,20], slip-dependent friction [27] and Coulomb friction [25].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Such instabilities typically result in rapid slip propagation along frictional interfaces, mediated by rupture modes [34][35][36][37][38][39][40][41][42][43][44][45][46]. Spatiotemporal rupture propagation modes can be generally classified into expanding cracklike rupture fronts and compact self-healing slip pulses [35][36][37][38][39][47][48][49][50][51]. In the former, v at an interfacial position behind the propagating mode remains finite as long as propagation persists, while in the latter, v vanishes over a finite time as propagation persists.…”
Section: Introductionmentioning
confidence: 99%